La internacionalización de la educación superior desde la perspectiva de estudiantes universitarios - Álvarez Ruíz, Liliana Patricia; Mendivil Hernández, Patricia; Herazo Chamorro, Mónica Isabel; Restrepo Ruíz, Marisela; González Sánchez, Eduardo; Álvarez Ruíz, Liliana Patricia; Mendivil Hernández, Patricia; Herazo Chamorro, Mónica Isabel; Restrepo Ruíz, Marisela; González Sánchez, Eduardo; Álvarez Ruíz, Liliana Patricia; Mendivil Hernández, Patricia; et al. (Corporación Universitaria Americana, 2024)
Introduction: Corporación Universitaria del Caribe-CECAR has been interested in creating internationalization spaces from academy, transforming its teaching-learning processes regarding the demands of the globalized world; this has allowed to develop and to strengthen, in these future professionals, the competences and abilities that fit the labor and social needs from the context they will work in. Objective: The current study aims at identifying practicum students’ perceptions towards higher education internationalization and describing the benefits of internationalization in such processes. Method: The applied methodology had a mixed descriptive approach; the data collection tools were the Likert scale to measure CECAR’s internationalization and the documentary revision. Results: Within results, it was evidenced that, in 2021-2, the 79% of practicum students has a positive attitude and only the 21% has a rejection attitude with regard to internationalization processes. Regarding its main benefits, is highlighted the critical thinking aspect that is developed on professionals which allow them to communicate assertively throughout diverse contexts and generating international academic networks. Conclusions: To conclude, undergraduates are interested in making part of internationalization activities, letting them to articulate their academic process with international experiences in their practicum requirement, in which they can strengthen their professional skills and competences